Tree Species Assessment at Lohgad and Visapur Fort - A Part of Western Ghats, Maharashtra (India) - Kulkarni, Amol V.; Mahajan, D. M.; Bhore, Ajit; Ghotkule, Kiran; Waghmare, Sambhaji (Indian Forester, 2015)
During the present investigations, tree species were documented from Lohgad and Visapur forts which occupy a small geographical area in Western Ghats (one of the important global biodiversity hotspots and UNESCO'SWorld heritage site) near Lonavala and Khandala hill stations. Tree species were identified and number of families, genera and species were recorded along with their endemic and threatened status. Literature survey was made as a source of secondary data for comparative account. In all 194 tree species belonging to 134 genus and 48 families were recorded. Moraceae was dominant family followed by Mimosaceae and Euphorbiaceae. Twenty six non-native cultivated species were recorded. From the results it is concluded that, Lohgad-Vispur forts region is highly diverse but under the anthropogenic threats due to various developmental projects (irresponsible tourists, construction of roads and other infrastructure) and introduction of non-native species. Due to rich diversity and well-nourished habitat for the wildlife, this region was proposed for Santapau Wildlife Sanctuary. If protected well, it could be the corridor and nourishing habitat for wildlife of the area.